2020
DOI: 10.3390/ijms21197221
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNAs: Crossroads between the Exposure to Environmental Particulate Pollution and the Obstructive Pulmonary Disease

Abstract: Environmental pollution has reached a global echo and represents a serious problem for human health. Air pollution encompasses a set of hazardous substances, such as particulate matter and heavy metals (e.g., cadmium, lead, and arsenic), and has a strong impact on the environment by affecting groundwater, soil, and air. An adaptive response to environmental cues is essential for human survival, which is associated with the induction of adaptive phenotypes. The epigenetic mechanisms regulating the expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 130 publications
(168 reference statements)
1
17
0
Order By: Relevance
“…Izzotti et al reported the first evidence of miRNA expression alterations caused by CS, namely downregulation of 24 miRNA involved in apoptosis, proliferation, and angiogenesis in lung [176]. The analysis of the miRNA pattern is important because miRNA senses the environmental stresses, causes phenotype changes in a cell-and tissue-specific way, being potentially used in prognostics, and contributes to the COPD pathogenesis [177,178].…”
Section: Genetic and Epigenetic Regulationmentioning
confidence: 99%
“…Izzotti et al reported the first evidence of miRNA expression alterations caused by CS, namely downregulation of 24 miRNA involved in apoptosis, proliferation, and angiogenesis in lung [176]. The analysis of the miRNA pattern is important because miRNA senses the environmental stresses, causes phenotype changes in a cell-and tissue-specific way, being potentially used in prognostics, and contributes to the COPD pathogenesis [177,178].…”
Section: Genetic and Epigenetic Regulationmentioning
confidence: 99%
“…Notably, exposure to the environment may alter epigenetics, including miRNA, resulting in the development of human pathological conditions in the future [71]. Several studies have shown that changes in specific miRNA expression profiles respond to numerous environmental pollutants, including organic pollutants, metals, radiation, cigarette smoke, pesticides, carcinogens, and air pollution [72]. Therefore, altered miRNA expression is likely to be a biomarker as a result of their sensitivity to environmental pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that traffic-related air pollution increases airway inflammation which induces the expression of inflammatory factors through the activation of the NF-κB signaling pathway [ 9 ]. Environmental exposure can also induce oxidative stress through a disruption in the expression of micro-RNA, short sequences of non-coding RNA molecules which are involved in the regulation of gene expression [ 10 ]. Increased oxidative stress in COPD patients, which has been convincingly demonstrated with various biomarkers, reflects both an increase in oxidant molecules and a decrease in antioxidant defense mechanisms [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%